Food Insecurity Versus Learners’ Performance in the Classroom: A Case of South African Rural School - Buthelezi, Michael Mbongiseni; Ncisana, Lusanda; Ntshangase, Mohammed Xolile (Research in Social Sciences and Technology, 2025)
Food insecurity is one of the less researched problems that poses a challenge to schools in South Africa. This qualitative study seeks to holistically explore this problem as it adopts Maslow’s hierarchy of needs and Vygotsky’s sociocultural theory as the lenses of exploration. In addition to socio-cultural beliefs on food and academic achievement, Maslow and Vygotsky offer a framework for physiological and cultural theories of how food impacts human brain function and capability. Therefore, this study's primary goal is to investigate the connection between food insecurity and academic achievement in rural South African schools, such as Tshehlo Secondary School in the Capricorn region of the province of Limpopo. Methodologically, this study purposively sampled grade 10,11, and 12 learners from Tshehlo secondary school for focus group discussions, observations, semi-structured interviews, and surveys from top to low achievers. The data collected were thematically analysed as they show that there is a link between food insecurity and learners’ performance in classrooms. Data was analysed to compare the experiences of top and low-performing learners with food insecurity and how it affects their performance in the classroom. Objectives of this study are; (a) to explore the effects of food insecurity on learners’ concentration and attention in the classroom, (b) to explore the impact of food insecurity on learners’ academic achievements, (c) to explore the relationship between food insecurity and learners’ performance in the classroom, (d) to explore any comparative difference between learners from food secure background and those who come from food insecure homes in terms of academic success. Recommendations thereof significantly include (a) devising ways to ensure food security programs in schools, (b) counselling and motivation in schools, and (c) DBE policy development and enforcement which involves even NGO’s with regards to learners’ nutrition. Conclusion entails that food security is more important for high quality achievements in schools as it directly impacts learners’ attitudes towards learning. Furthermore, it is challenging to evaluate the long-term educational effects of food poverty because a large number of the research are cross-sectional rather than longitudinal in character.